Approche des relations des visiteurs à l’espace : une expérience du paysage - Anne-Sophie Devanne (Projets de Paysage)
Our doctoral research, which focuses on space experience of mountain hikers, rests on the premise that both landscape and tourism experience are privileged entrances to understanding human relationship with space. In this paper, we discuss the theoretical and methodological framework of this doctoral research. Our theoretical framework is built on three main concepts: geographical consciousness, spiral and landscape as a social construction. Once defined these three concepts, we can identify key features of hikers’ landscape experience. Then, we propose a qualitative and phenomenological method that allows us to collect hikers’ testimony and to understand the meanings they attribute to visited landscapes.